2009
DOI: 10.1016/j.clim.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized lipids enhance RANKL production by T lymphocytes: Implications for lipid-induced bone loss

Abstract: Osteoporosis is a systemic disease that is associated with increased morbidity, mortality and health care costs. Whereas osteoclasts and osteoblasts are the main regulators of bone homeostasis, recent studies underscore a key role for the immune system, particularly via activation-induced T lymphocyte production of Receptor Activator of NFκB Ligand (RANKL). Well-documented as a mediator of T lymphocyte/dendritic cell interactions, RANKL also stimulates the maturation and activation of bone-resorbing osteoclast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 78 publications
3
67
1
6
Order By: Relevance
“…This RANKL induction appears to be modest but it suggests an additional source of RANKL in the vasculature. The findings are also consistent with our previous study that shows induction of RANKL in T lymphocytes by minimally modified lipoprotein particles (20), of which ox-PAPC is a biologically active, phospholipid component (31,32). These findings suggest that ox-PAPC is molecular component that is largely responsible for biological activities of minimally modified lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This RANKL induction appears to be modest but it suggests an additional source of RANKL in the vasculature. The findings are also consistent with our previous study that shows induction of RANKL in T lymphocytes by minimally modified lipoprotein particles (20), of which ox-PAPC is a biologically active, phospholipid component (31,32). These findings suggest that ox-PAPC is molecular component that is largely responsible for biological activities of minimally modified lipoproteins.…”
Section: Discussionsupporting
confidence: 93%
“…We previously found that RANKL expression is increased in calcified cartilaginous metaplasia in atherosclerotic lesions of hyperlipidemic mice (19). RANKL expression is also increased by minimally modified low-density lipoprotein in T lymphocytes (20). Kaden et al (21) have previously shown that treatment of human aortic valvular cells with soluble RANKL promotes osteoblastic differentiation and matrix calcification.…”
mentioning
confidence: 94%
“…Of interest, upregulation of RANKL was found in circulating T cells of patients with acute coronary syndrome (ACS) (unstable angina/myocardial infarction) as compared to subjects with stable coronary artery disease [9]. More recently, researches by Graham et al [15] demonstrated that exposure of T cells to oxidized lipids is accompanied by increased expression of RANKL in the cells. The same group also showed that RANKL was upregulated in the bone marrow and splenic T cells of mice that develop osteopenia when fed high-fat diet [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a number of studies indicated that the accumulation of lipid oxidation products within the skeleton may contribute to pathological bone resorption, mainly through the inhibition of osteoblast differentiation and the induction of osteoclast maturation/activation [14]. Of interest, data are available showing that oxidized lipids can induce RANKL expression in T cells [15] and that RANKL is increased in bone marrow and splenic T cells of mice with hyperlipidemia-induced bone loss [16]. No data are available so far showing whether lipid-lowering strategies can modulate in vivo OPG/RANK/RANKL expression in immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized lipids were reported to inhibit osteoblasts differentiation [14,15], reduce their viability [13] and increase their apoptosis [16]. They were also found to affect bone resorption by increasing osteoclastogenesis cytokines production such as receptor activator of nuclear factor-κB (RANKL) and interleukin-6 from both T-lymphocytes and osteoblasts [17][18][19][20][21]. Furthermore, it has been reported that oxidized lipids down regulate parathyroid hormone receptor (PTH1R) in osteoblasts causing resistance to PTH [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%